Identifying Changepoints in Biomarkers During the Preclinical Phase of Alzheimer’s Disease - Younes, Laurent; Albert, Marilyn; Moghekar, Abhay; Soldan, Anja; Pettigrew, Corinne; Miller, Michael I. (Frontiers in Aging Neuroscience, 2019)
Abstract Objective: Several models have been proposed for the evolution of Alzheimer’s disease (AD) biomarkers. The aim of this study was to identify changepoints in a range of biomarkers during the preclinical phase of AD. Methods: We examined nine measures based on cerebrospinal fluid (CSF), magnetic resonance imaging (MRI) and cognitive testing, obtained from 306 cognitively normal individuals, a subset of whom subsequently progressed to the symptomatic phase of AD. A changepoint model was used to determine which of the measures had a significant change in slope in relation to clinical symptom onset. Results: All nine measures had significant changepoints, all of which preceded symptom onset, however the timing of these changepoints varied considerably. A single measure, CSF-tau, had an early changepoint (40 years prior to symptom onset). A group of measures, including the remaining CSF measures (CSF-Abeta and phosphorylated tau) and all cognitive tests had changepoints 10-15 years prior to symptom onset. A second group is formed by medial temporal lobe shape composite measures, with a five-year time difference between the right and left side (respectively nine and three years prior to symptom onset). Conclusions: These findings highlight the long period of time prior to symptom onset during which AD pathology is accumulating in the brain. There are several significant findings, including the early changes in cognition and the laterality of the MRI findings. Additional work is needed to clarify their significance.